(untitled) (International Journal of Engineering and Computer Science, 2013)
With the increase use of video data sets for multimedia-based applications has created a demand for database technology that is capable of storing digital video in the form of video databases and providing efficient methods for handling the content based query and retrieval of video data. Traditional methods for handling data storage, query processing and retrieval cannot be extended to provide this functionality for video. In this paper, we have described the VDBMS which is a research platform for video database, a system that supports comprehensive and efficient database management for digital video. Video query processing presents significant research challenges, mainly associated with the size, complexity and unstructured nature of video data. This paper also presents the video query processing functionality of VDBMS using several query processing algorithms. It also focuses on how VDBMS supports query processing for content-based query, search and retrieval of video data. In this paper, we have addressed query processing issues in two contexts, first as applied to the video data type and second as applied to the stream data type. Our paper also describes two query operators for the video data type which implement the rank-join and stop-after algorithms. Lastly this paper also presents the stream query processing framework of VDBMS.